Determinant of Water Source Contamination by Soil Transmitted Helminths in Rural Areas of Jember District - Armiyanti, Yunita; Mash’ab Zirrun Al-Qomah; Angga Mardro Raharjo; Bagus Hermansyah; Wiwien Sugih Utami (BKM Public Health and Community Medicine, 2024)
Purpose: This study aims to identify STH eggs and larvae that contaminate water sources in rural areas of Jember and their risk factors. Method: This type of study is an observational analytic study with a cross-sectional approach. Samples from water sources in Mumbulsari and Sukowono districts were taken on inclusion criteria under flotation and sedimentation methods and totaled 56 samples. Respondents were interviewed on account of risk factors related to the presence of STH in water sources using a questionnaire and a total of 56 respondents. Result: The results showed that the common type of STH found was Hookworm (92.31%). The most polluted water source is river (53.84%). Based on the characteristics, the majority of respondents are female (67.86%), aged over 40 years (58.93%), have low education (57.15%), and have no job (51.79%). Found a relationship using chi-square between bowel habits and the presence of STH eggs and larvae (ρ > 0.05). Conclusion: This study proved that STH eggs and larvae can contaminate water sources such as rivers and wells The contamination is related to the habit of defecating not in latrines, so the important prevention for STH infection in water sources is to change the habit of defecation into a healthy habit.